1D Numerical Code for Methane Dynamics in Thawing Permafrost - Kehua You (Zenodo, 2023)
This is a numerical modeldeveloped fora manuscript ( Biodegradation of Ancient Organic Carbon Fuels Seabed Methane Emission at the Arctic Continental Shelves )to be submitted to the Journal of Geophysical Research - Global Biogeochemical Cycles. It is written in MatLab. This model is aone-dimensional multiphase flow multicomponent reactive transport numerical model used to investigate the stabilities of the carbon pools, frozen organic carbon and methane hydrate, within the thawing permafrost at the Arctic continental shelves since the Last Glacial Maximum. This model simulates the following coupled processes:1) the top-down heat transport from the seafloor and the bottom-up heat flow from geothermal heat supply, 2) the temperature-salinity dependent ice melting, 3) the temperature-dependent organic carbon biodegradation and methanogenesis, 4) the methane transport by free gas flow and by diffusion and advection with liquid water flow, and 5) the pressure-temperature-salinity dependent methane hydrate dissociation. The outputs of this model include the depth distribution and the time evolution of the (1) sediment temperature, (2) pore water pressure, (3) pore water salinity, (4) ice stable zone, (5) methane hydrate stable zone, (6) ice saturation, (7) methane hydrate saturation, (8) free methane gas saturation, (9) liquid water saturation, (10) organic carbon content with high reactivity, (11) organic carbon content with low reactivity, (12) microbial methane production rate from biodegradation of organic carbon, and (13) seabed methane emission rate. Simulations should be started from the file named "Main_loop". Initial conditions, boundary conditions and other input parameters are specified in "Initialization". Pressure and Temperature at the top of the boundary should also be edited in "Main_loop". Detailed information about the model could be found in the paper Biodegradation of Ancient Organic Carbon Fuels Seabed Methane Emission at the Arctic Continental Shelves.